Learning new innovative methodologies used in covid-19 times - Rodriguez Calzada, Lorena (Journal of Management and Business Education, 2021)
Currently, online or hybrid teaching are increasingly in demand and have been driven by social, demographic and health factors such as that experienced during the global COVID-19 pandemic. The traditional classroom as originally was conceived has expanded both its temporal and physical limitations. This text shows how new innovative methodologies have been developed through different applications such as Wooclap or Gamification works, with the main objective of checking the perception, motivation and satisfaction of students. These are useful tools for teachers to get an easy and fast feedback from students. Two hypotheses are also presented, which will be contrasted with the analysis of the grades of the final tests of the 2019/2020 academic year and several questionnaires, with a high response ratio (88.33%), but with a small sample (60 subjects), where it has been found that the students adapt to the methods previously exposed. The main conclusion is the following: students adapt to remote teaching, they get involved in the subject and spend time learning, they are motivated to use innovative techniques, they show interest and participation in them.